Is social capital part of the institutions continuum and is it a deep determinant of development? - Stephen Knowles (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
There is a growing literature which analyses, using cross-country data, whether institutions or geography is the most important deep determinant of economic development. The empirical proxies for institutions used in this literature focus on the definition of institutions, formal and informal. This study argues that the concept of informal institutions is similar to social capital. However, the social capital and `institutions as a deep determinant' literatures rarely acknowledge the existence of the other. It is argued that social capital meets the criteria for being a deep determinant of development and that both the cross-country literature on social capital, and the deep determinants of development literature, could be enriched by empirically modelling social capital as a deep determinant of development.
Keywords: Z13; O11; 330; social capital; institutions; determinants of development; Entwicklung; Social Capital